On the relationship between technical debt management and process models (2021)
—As technical debt (TD) potentially occurs as a result of poor decisions that affect software development tasks, one might expect that practitioners following different process models, such as agile, hybrid or traditional, will perceive and manage the effects of TD differently. This study investigates the potential relationship between development process models and TD effects and their management by surveying 432 practitioners from software organizations in Brazil, Chile, Colombia, and the United States. Results indicate that, although opinions about debt prevention and repayment are the same regardless of the process model, there are differences in how practitioners monitor and feel the effects of TD. Development teams can use our findings to have a clearer view of the possible effects and managerial influence of TD in their projects for each type of process model.